Promoting Entrepreneurship in Rural Areas : Need of the Hour - Gupta, Radha (Prabandhan: Indian Journal of Management, 2011)
The paper deals with the question of how to create a strong economy of a nation, when a society comprises of people with wide disparity in their income level, concentrating economic power in the hands of few. When one strata of the population, with high income levels, lives in urban areas, it creates more demand, resulting in more industrialization because people have the ability as well as the willingness to spend. Albeit, the rural sector is showing tremendous growth in agriculture, but this alone will not serve the purpose. Need of the hour is to have more industries in rural areas for socio-economic growth, and to benefit from efficiency, capability and accountability of human resources available in this area. Not only this, more is required to be done for creating an urge and developing entrepreneurship spirit among rural people, because entrepreneurship is considered to be the key driver for pulling up the economic engine of a nation, and that is why, nations, regions and communities that actively promote entrepreneurship activities for economically challenged people demonstrate much higher growth rates and consequently, lead to higher levels of development than nations, regions and communities whose institutions, politics and culture hinder entrepreneurship and where rural industrialization is of no concern. An entrepreneurial economy, whether on the national, regional or community level, differs significantly from a non-entrepreneurial economy in many respects, not only by its vibrant economic structure and socio-economic growth, but also by the quality of life, which it offers by creating more and better employment opportunities. The aim of this paper is to analyse how formal education and informal learning can develop entrepreneurship skill and create an urge in an entrepreneur for starting an enterprise. The paper further highlights rural distinctiveness to be a sharp edged weapon for creating an environment for entrepreneurship, because rural youth can benefit from local resources and carve their own niche. In the end, certain suggestions have also been made for fostering rural entrepreneurship in rural segment of the society.